IMPLEMENTATION OF 4D BUILDING INFORMATION MODELING (BIM) ON THE FLAT BUILDING PROJECT OF BBPJN XI/PJN I KALIMANTAN - Akhmad Hafizurahman; Husnul Khatimi (CERUCUK, 2022)
The BBPJN XI/PJN I Kalimantan Flats construction project only applies manual scheduling in the form of an S curve. This building consists of 9 floors with reinforced concrete material. Currently, there is BIM technology that can minimize problems caused by manual scheduling in controlling time. So in this study, a study will be conducted on the application of 4D BIM-based project scheduling using the Tekla Structures 2020 software from manual project scheduling.The building modeling refers to the plan drawings, including piling and reinforced concrete structural work in the Tekla Structures 2020 software. Scheduling is made using the Task Manager extension found in Tekla referring to the RAB, S curve, and interviews with the project party. The modeling results are then inputted into the Task Manager to provide 4D visualization with the help of the Object Representation extension combined with the Project Status Visualization extension.Based on the results of monitoring project progress (tracking) inputted into the Task Manager, it is known that lower structural work was completed two weeks earlier. Upper structural work started from the ground floor starting one week earlier, and all structural work was completed 16 days earlier than scheduled plan. The duration of the work generated by Tekla Structures 2020 is 126 calendar days. The work starts from October 19, 2020, to February 21, 2021. So, with several extensions owned by Tekla, it can be said that the use of Tekla Structures 2020 software in the implementation of 4D BIM can be relied on for monitoring and minimizing errors in scheduling.